Incomplete block of NMDA receptors by intracellular MK-801. (December 2018) - Sun, Weinan; Wong, Jonathan M.; Gray, John A.; Carter, Brett C.
Abstract: NMDA receptors (NMDARs) are essential components in glutamatergic synaptic signaling. The NMDAR antagonist MK-801 has been a valuable pharmacological tool in evaluating NMDAR function because it binds with high affinity to the NMDAR ion channel pore and is non-competitive with ligand binding. MK-801 has also been used to selectively inhibit NMDAR current in only the cell being recorded by including the drug in the intracellular recording solution. Here, we report that intracellular MK-801 (iMK-801) only partially inhibits synaptic NMDAR currents at +40 mV at both cortical layer 4 to layer 2/3 and hippocampal Schaffer collateral to CA1 synapses. Furthermore, iMK-801 incompletely inhibits heterologously expressed NMDAR currents at −60 mV, consistent with a model of iMK-801 having a very slow binding rate and consequently ∼30, 000 times lower affinity than MK-801 applied to the extracellular side of the receptor. While iMK-801 can be used as a qualitative tool to study reduced postsynaptic NMDAR function, it cannot be assumed to completely block NMDARs at concentrations typically used in experiments. Highlights: Intracellular MK-801 does not completely block synaptic NMDAR current. Heterologously expressed NMDARs also show incomplete inhibition by iMK-801. Modeling indicates a ∼30, 000 fold lower affinity for intracellular MK-801.